Karakterisasi Metalurgi Camshaft Non-OEM Menggunakan Uji Komposisi Kimia dan Kekerasan Surface Hardening - Sigit Setijo Budi; Andre Budhi Hendrawan (CV. IRA PUBLISHING, 2025)
This study aims to evaluate the metallurgical characteristics of Non-OEM camshafts through chemical composition analysis and surface hardness testing, and to compare them with a reference camshaft manufactured from VCN150 steel. All samples were tested in the as-received condition to represent actual manufacturing quality in the market. Chemical composition was analyzed using Optical Emission Spectroscopy (OES), while surface hardness distribution was measured using the Rockwell C method in accordance with ASTM E18. The results show that the Non-OEM A camshaft exhibits the highest surface hardness (≈60–61 HRC) with a steep decrease toward the core, whereas the Non-OEM B camshaft reaches approximately 56–57 HRC with a more uniform hardness profile. The reference camshaft demonstrates a surface hardness of about 60 HRC with a gradual decrease toward the core. Variations in carbon and alloying elements contribute to differences in hardening response. These findings indicate variable material quality among Non-OEM camshafts compared with industrial-grade materials.